2020
DOI: 10.1126/science.abb3377
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-recognizing motifs in plant LysM receptors are major determinants of specificity

Abstract: Plants evolved lysine motif (LysM) receptors to recognize and parse microbial elicitors and drive intracellular signaling to limit or facilitate microbial colonization. We investigated how chitin and nodulation (Nod) factor receptors of Lotus japonicus initiate differential signaling of immunity or root nodule symbiosis. Two motifs in the LysM1 domains of these receptors determine specific recognition of ligands and discriminate between their in planta functions. These motifs define the ligand-binding site and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 52 publications
(79 reference statements)
2
74
0
1
Order By: Relevance
“…2). The promiscuity of S. flavescens might be related to its receptor specific to Nod factor (NF) in the surface of root cells, as these receptors are related greatly to the microsymbiont spectrum of the host legumes (Bisseling and Geurts 2020;Bozsoki et al 2020). The importance of ligand-recognizing motifs in plant receptors' interaction with microbe-associated molecular pattern (MAMP) will be explained in subsequent section.…”
Section: Specificity Vs Promiscuity Of Rhizobia and Legumesmentioning
confidence: 99%
“…2). The promiscuity of S. flavescens might be related to its receptor specific to Nod factor (NF) in the surface of root cells, as these receptors are related greatly to the microsymbiont spectrum of the host legumes (Bisseling and Geurts 2020;Bozsoki et al 2020). The importance of ligand-recognizing motifs in plant receptors' interaction with microbe-associated molecular pattern (MAMP) will be explained in subsequent section.…”
Section: Specificity Vs Promiscuity Of Rhizobia and Legumesmentioning
confidence: 99%
“…The coding of avocado UniGenes to pattern recognition receptors (PRRs) was performed based on their A. thaliana homologs (Nürnberger & Kemmerling, 2006) and the presence of the LysM motif in some of them (Bozsoki et al, 2020) was confirmed through the Pfam annotation.…”
Section: Identification Of Avocado Immune Receptorsmentioning
confidence: 99%
“…Due to the presence of the LysM domain, it has been speculated that these proteins can recognize glycoproteins and presumably participate in their degradation (Zhang, Cannon & Stacey, 2009). Moreover, recently, in Lotus japonicas, receptors associated with nodulation factors and chitin were found to have a very similar structure but contain two diverging motifs in the LysM1 domain that are necessary for discriminating between immunity and symbiotic functions (Bozsoki et al, 2020).…”
Section: Avocado Immune Receptors Expression During F Kuroshium Interactions and In The Resistosomementioning
confidence: 99%
“…Interactions between the host and microbes are shaped by multiple factors associated with host immunity, phylogeny, environmental features (e.g., pH, presence of biotic or abiotic compounds, temperature), diet and nutrient availability (Brinker et al, 2019).…”
mentioning
confidence: 99%